The protective effect of Paliasa (Kleinhovia hospita L.) leaf extract against elevated total bilirubin serum induced by toxic dose of antituberculosis in rats - Yulia Yusrini Djabir; Imelda Dhea Meylin; Rosany Tayeb (Faculty of Medicine, Hasanuddin University., 2019)
Liver dysfunction is implicated with the use of Antituberculosis (AT) leading to low compliance of TB patients to AT regimen. One of biomarker that is important to measure liver dysfunction is total bilirubin serum. Paliasa leaves have been emiprically used to improve liver function in South Sulawesi. This study aimed to determine the effect of ethanolic extract of Paliasa leaves on total bilirubin serum in rats. Twenty rats were devided into five groups: Group I served as the healthy control was only given NaCMC suspension, group II was treated with 178 mg/200gBB of AT suspension, while group III, group IV and group V were given Paliasa extract 125 mg/kgBB, 250mg/kgBB and 500 mg/kgBB, respectively, 4 hours prior to AT suspension administration. Treatments were performed once a day for 28 days. Blood sampling was carried out 24 hours following the last treatment. The total bilirubin levels were measured using Humalyzer 3500. The results showed that the administrations of AT suspension for 28 days significantly increased rat total bilirubin levels. Paliasa leaf extract in all given dose was able to reduce the total bilirubin levels of rats compared to the group given only AT suspension. However, statistical significance was only reached by the groups that were treated with Paliasa extract 250 and 500 mg/kgBB. Therefore it is concluded that ethanol extract at a dose of 250 and 500 mg/kgBB has protective effect against AT-induced elevation of total bilirubin serum in rats.